A Comparative Study of the Usability of Two Object-oriented Concurrent Programming Languages - Nanz, Sebastian; Torshizi, Faraz; Pedroni, Michela; Meyer, Bertrand (arXiv.org, 2010)
Concurrency has been rapidly gaining importance in general-purpose computing, caused by the recent turn towards multicore processing architectures. As a result, an increasing number of developers have to learn to write concurrent programs, a task that is known to be hard even for the expert. Language designers are therefore working on languages that promise to make concurrent programming "easier" than using traditional thread libraries. However, the claim that a new language is more usable than another cannot be supported by purely theoretical considerations, but calls for empirical studies. In this paper, we present the design of a study to compare concurrent programming languages with respect to comprehending and debugging existing programs and writing correct new programs. A critical challenge for such a study is avoiding the bias that might be introduced during the training phase and when interpreting participants' solutions. We address these issues by the use of self-study material and an evaluation scheme that exposes any subjective decisions of the corrector, or eliminates them altogether. We apply our design to a comparison of two object-oriented languages for concurrency, multithreaded Java and SCOOP (Simple Concurrent Object-Oriented Programming), in an academic setting. We obtain results in favor of SCOOP even though the study participants had previous training in Java Threads.